Clinical and anamnestic evaluation rôle for the diagnosis and treatment of families affected by Lynch syndrome. Case report and review of the literature - Cudia, Bianca; Liccardo, Raffaella; Di Carlo, Giovanni; Damiano, Giuseppe; Lo Monte, Attilio Ignazio; Izzo, Paola; Duraturo, Francesca (European Journal of Oncology and Environmental Health, 2015)
The Lynch syndrome increases the chances of developing cancer in individuals at risk, so prevention by instrumental screening of the more frequent cancers becomes very important. Genetic testing allows us to diagnose the disease with certainty and to identify individuals at risk. However, there are also reliable clinical and anamnestic criteria by which to diagnose the syndrome. The clinical case reported in our study shows that, in the absence of genetic characterization, clinical criteria alone rapidly suggested the correct approach leading to early treatment of relatives in the case in point.